TINGKAT KESUKARAN DAN SEBAB-SEBAB KESUKARAN KEPALA SEKOLAH DALAM MELAKSANAKAN PEMBINAAN GURU SMA/MA SE- KOTA ENDE - Yosef Moan Banda (STIT PRINGSEWU, 2023)
This study aimed to know the level of, and in fact, principals' difficulty in administering teacher coaching of SMA/MA in Ende. The research type was descriptive. The questionnaire data were distributed to 12 principals as the respondent. Data were analyzed by using a descriptive quantitative approach with a cross-tabulation technique. The result shows that in administering teaching coaching of SMA/MA in Ende, every aspect listed in the difficulty level can be categorized as very difficult. The result of the data analysis of causes of adversity shows that the principles of administering teacher coaching of SMA/MA in Ende found out: 1) The aspect of class visits was the average of 21,58% caused the time limitation; 2) The aspect of the personal meeting was the average 14,64% caused the professional abilities; 3) The aspect of the teacher council meeting was the average of 27,13% caused limited execution instructions; 4) The aspect of school inter-school visits was average of 18,58%, causing a minimum of expense; 5) The aspect of the teacher work group was an average of 17,03%, causing a minimum expense and time limit. Thus, the dominant cause of adversity was the limitation of the time limit.